«En cuadrilla»: the graffiti as a source for the study of the working environment in the production of amphorae in Baetica. A new methodological approach - Bermúdez Lorenzo, Juan Manuel; Caballero Payá, Daniel (Huarte de San Juan. Geografía e Historia, 2024)
The aim of this paper is to present the linking of data from amphorae graffiti with other Dressel 20 inscriptions found on Monte Testaccio in Rome by using the data contained in the Roman Open Data website, which allows the extraction of results obtained thanks to the use of the SPARQL language. This exercise makes it possible to date and assign the production provenance of the graffiti located there. The aim is to offer an example of the work methodology that can be carried out with this tool from the source that amphoric epigraphy represents for the study of the social history of Ancient Rome.
Keywords: amphoric epigraphy; Dressel 20; Testaccio; ancient graffiti